Gênese e micromorfologia de solos crioturbados na antártica marítima - Araújo, Nadeline Hevelyn de Lima (Universidade Federal do Rio Grande do Norte, 2021)
Maritime Antarctica, as an environment of high climate sensitivity, represents a laboratory scenario for the glimpse of soil formation, expressing weathering processes and biogeochemical dynamics in unique conditions on the planet. The primary engine is the freezing/thawing processes, and in the second instance the formation of permanently frozen soils, known as permafrost. Antarctic soils are directly linked to thermal phenomena, which causes ablation of glaciers, causing relief modeling processes and consequent pedological structuring. In general, the soils of Antarctica are shallow and incipient and the ornithogenic areas are an exception to the rule, where the deepest soils are found, with greater performance of chemical weathering. However, the Byers Peninsula, as one of the largest ice-free areas, inserted in a climatic context with atypical liquid precipitation for the Maritime Antarctic environment, is dominated by cryoturbation features, even in soils without detection of permafrost, demonstrating that water acts as a the sine qua non for cryoturbation processes in Antarctic soils. Coordenação de Aperfeiçoamento de Pessoal de Nível Superior - CAPES A Antártica Marítima enquanto um ambiente de alta sensitividade climática, representa um cenário laboratorial para o vislumbre da formação de solos, exprimindo processos intempéricos e uma dinâmica biogeoquímica em condições únicas no planeta. Tendo como motor primário os processos de congelamento/descongelamento, e em segunda instância a formação de solos permanentemente congelados, designados como permafrost. Os solos Antárticos estão diretamente ligados à fenômenos térmicos, que provocam ablação das geleiras, ocasionando processos modeladores do relevo e conseguinte estruturação pedológica. No geral, os solos da Antártica são rasos e incipientes e as áreas ornitôgênicas são excessão à regra, onde se encontram os solos mais profundos, tendo maior atuação do inteperismo químico. Entretanto, a Península Byers, como uma das maiores áreas livres de gelo, ...